2021
DOI: 10.4103/jpn.jpn_84_20
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long-term antiepileptic therapy on carotid artery intima-media thickness

Abstract: A BSTRACT Background: Common first-line antiepileptic drugs (AEDs) used in children are valproate, phenytoin, and levetiracetam. Many side effects for these AEDs are reported including obesity, atherosclerosis, and metabolic syndrome. The aim of our study was to evaluate changes in carotid artery intima-media thickness (CIMT) in epileptic children and to correlate with lipid profile of those who are on long-term antiepileptic therapy. Materials and Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 19 publications
3
5
0
Order By: Relevance
“…57,58 Karatoprak et al, 2020, and Kolekar et al, 2021, concluded that non-obese children with epilepsy who receive monotherapy of valproic acid or levetiracetam may be at higher risk of developing subclinical atherosclerosis despite a normal lipid profile. 27,59 In our study, we found significant positive correlations between CIMT and TC, triglyceride, and LDL. Also, we found a significant negative correlations between CIMT and HDL.These findings are comparable to Kolekar et al, who reported similar correlations between CIMT and individual lipid profiles.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…57,58 Karatoprak et al, 2020, and Kolekar et al, 2021, concluded that non-obese children with epilepsy who receive monotherapy of valproic acid or levetiracetam may be at higher risk of developing subclinical atherosclerosis despite a normal lipid profile. 27,59 In our study, we found significant positive correlations between CIMT and TC, triglyceride, and LDL. Also, we found a significant negative correlations between CIMT and HDL.These findings are comparable to Kolekar et al, who reported similar correlations between CIMT and individual lipid profiles.…”
Section: Discussionsupporting
confidence: 65%
“…Our results were consistent with other studies. 26,27,32 Also, we observed that with increasing age, the values of CIMT increased as well. However, no significant difference in the mean CIMT between males and females as reported in other studies.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Both Karatoprak et al, 2020, and Kolekar et al, 2021, concluded that non-obese children with epilepsy who receive monotherapy of valproic acid or levetiracetam alone may be at higher risk of developing subclinical atherosclerosis despite a normal lipid profile [ 28 , 29 ]. This might be linked to atherosclerotic alterations, and these children will need to be closely monitored to avoid cardiovascular and cerebrovascular risks [ 29 ].…”
Section: Discussionmentioning
confidence: 99%